2019
DOI: 10.1039/c9cc07889d
|View full text |Cite
|
Sign up to set email alerts
|

One-pot, two-step synthesis of unnatural α-amino acids involving the exhaustive aerobic oxidation of 1,2-diols

Abstract: Fluorescent, photoactivatable, and other functional amino acids were efficiently synthesized by a one-pot, two-step protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This process was shown to be quite efficient to perform deracemization, dynamic thermodynamic resolution, or (S) to (R) interconversion of unprotected α- [40][41][42] and β-AAs. 43 In this work, we examine the application of this methodology for asymmetric synthesis of (S)-α-(octyl)glycine, [44][45][46][47][48][49] a characteristic representative of naturally occurring class of lipidic α-AAs serving as key structural units in the design of lipophilic analogs of various biologically active peptides, such as enzymes, hormones, and therapeutic drugs. [50][51][52][53][54][55] For this work, we selected tri-dentate ligand 5 (Scheme 2) and the corresponding glycine complex 6, which show enhanced stereocontrolling properties due to a parallel displaced type of aromatic interactions between the selectively chlorinated o-amino-benzophenone and Pro N-benzyl rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process was shown to be quite efficient to perform deracemization, dynamic thermodynamic resolution, or (S) to (R) interconversion of unprotected α- [40][41][42] and β-AAs. 43 In this work, we examine the application of this methodology for asymmetric synthesis of (S)-α-(octyl)glycine, [44][45][46][47][48][49] a characteristic representative of naturally occurring class of lipidic α-AAs serving as key structural units in the design of lipophilic analogs of various biologically active peptides, such as enzymes, hormones, and therapeutic drugs. [50][51][52][53][54][55] For this work, we selected tri-dentate ligand 5 (Scheme 2) and the corresponding glycine complex 6, which show enhanced stereocontrolling properties due to a parallel displaced type of aromatic interactions between the selectively chlorinated o-amino-benzophenone and Pro N-benzyl rings.…”
Section: Introductionmentioning
confidence: 99%
“…This process was shown to be quite efficient to perform deracemization, dynamic thermodynamic resolution, or ( S ) to ( R ) interconversion of unprotected α‐ 40–42 and β‐AAs 43 . In this work, we examine the application of this methodology for asymmetric synthesis of ( S )‐α‐(octyl)glycine, 44–49 a characteristic representative of naturally occurring class of lipidic α‐AAs serving as key structural units in the design of lipophilic analogs of various biologically active peptides, such as enzymes, hormones, and therapeutic drugs 50–55 …”
Section: Introductionmentioning
confidence: 99%
“…The commonly employed syntheses are restricted to a few strategies that usually involve tedious procedures and/or low conversions. [10] Enzymatic resolution does not provide a definitive solution due to the waste of a proportion of the products obtained, [11][12][13] although biocatalysis does provide an elegant solution. [14][15][16][17] Due to the high value of the final species, the development of efficient alternative procedures is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In 1934, Herbst and Engel reported thermally promoted biomimetic transaminations between α-keto acids and 2-phenylglycine without any catalysts to form the corresponding unprotected α-amino acids (Scheme a) . Although related research has been reported, the methods have not been applied to organic synthesis. , Intrigued by the potential usefulness of transamination, we recently reported a modified protocol . Combining transamination with the oxidation of 1,2-diols to α-keto acids, we established a direct method for the synthesis of unprotected α-amino acids.…”
Section: Introductionmentioning
confidence: 99%